Synthesis and electrical properties of novel pyrochlores in the Bi₂O₃-Fe₂O₃-M₂O₅ (M = Nb, Ta and Sb) ternary systems - Jusoh, Farah Aishah (2020)
Herein we report the synthesis and characterisation of novel pyrochlores in the Bi2O3-Fe2O3-M2O5 (M = Nb, Ta and Sb) ternary systems. Bi-containing pyrochlores are of great research interest to its low firing and interesting electrical properties. The subsolidus cubic pyrochlore phases with the proposed formula of Bi3.36Fe2.08+xM2.56-xO14.56-x (M = Nb, Ta and Sb) were prepared via conventional solid-state method in the temperature range 925 to 975 ˚C over 2 days. The solid solution mechanism was proposed to be a one-to-one replacement of M5+ by Fe3+ with considerable oxygen non-stoichiometry in the pyrochlore structure. The solid solution limits, as confirmed by x-ray diffraction (XRD) analysis, were (-0.24 ≤ x ≤ 0.48), (-0.32 ≤ x ≤ 0.48) and (0 ≤ x ≤ 0.64) for the Nb-, Ta- and Sb-analogues, respectively. These prepared samples crystallised in a cubic structure with a space group of Fd3m (No. 277). The refined lattice parameters, a = b = c of these pyrochlores showed no significant difference with increasing Fe3+ content and their values were found to be in the range 10.5065 (4)-10.5079 (5) Å, 10.4979 (8)-10.5033 (1) Å and 10.4284 (8)-10.4513 (8) Å for the Nb-, Ta- and Sb-analogues, respectively. The crystallite sizes calculated using both Scherrer and Williamson-Hall methods were found to be in the range 46.3-78.1 nm. Meanwhile, the surface morphologies of these pyrochlores showed a broad distribution of the grain size. All samples are confirmed to have correct chemical stoichiometries by inductively coupled plasma optical emission spectroscopy (ICP-OES). The thermal analyses showed all samples were thermally stable as neither phase transition nor weight loss was observed. On the other hand, five phonon modes due to the metal-oxygen bonds were found in the Fourier transform infrared spectroscopy (FT-IR) spectra of Bismuth Iron Niobate (BFN) and Bismuth Iron Tantalate (BFT) series; whilst, only three infrared-active phonon modes were detected in the Bismuth Iron Antimonate (BFS) solid solution. All the pyrochlores exhibited moderate dielectric constants in the range ~23-150 and low dielectric losses, in the order of 10-1 at 1 MHz and ~30 ˚C. The Arrhenius conductivity plots of these Nb-, Ta- and Sb- pyrochlore series showed a linear and reversible characteristic over the heat-cool cycle. In addition, the specific capacitances of all samples were determined by cyclic voltammetry (CV) and galvanostatic charge-discharged (GCD). The calculated specific capacitances by both methods indicated an insignificant variation among samples within the series as the values were less influenced by the Fe content.